Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2024)
The first paper investigates the nature and the characteristics of museum theater in Greece, as they have been formulated in experts' opinions related to the specific topic. The following paper discusses a tool that could assist the academic libraries in upgrading their Research Repositories with auto-enrichment capabilities, saving valuable labour time from their staff. This tool concerns data extraction from the four popular citation indexes (Scopus, Google Scholar, Web of Science and PubMed) and the ORCID service and can provide integrated management of multiple citation indexes, namely the collection of data per researcher and the application of deduplication algorithms so that a list of unique publications is obtained for each one of them. The Institutional Repository of the Cyprus University of Technology has been selected as a testbed, and all universities can undoubtedly utilize the obtained results. more efficient as it allows users to repeatedly access. However, during the COVID-19 pandemic, what is left for private copying except the situ access of users has been prohibited or suspended by law. The last paper portrays the city of Chalkida through the eyes of a poet, a novelist who identified with this city and is none other than Giannis Skaribas. The themes that fertilize the literary and poetic universe of Scarimba are inextricably linked to this city, and are necessarily filtered through the plot, the narration of the various phases of his work and the action in it. What is interesting is that Chalkida in Scarimba's work has nothing to do with Chalkida on the geographical map. Somewhat as if only the atmosphere of the city of the time as perceived by the author as a tool of narration of his mental processes, and his mental temperament.